2010
DOI: 10.1021/ja908827z
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nanosheets and Their Self-Assembled Regular Stacking Structure

Abstract: Silicon nanomaterials are encouraging candidates for application to photonic, electronic, or biosensing devices, due to their size-quantization effects. Two-dimensional silicon nanosheets could help to realize a widespread quantum field, because of their nanoscale thickness and microscale area. However, there has been no example of a successful synthesis of two-dimensional silicon nanomaterials with large lateral size and oxygen-free surfaces. Here we report that oxygen-free silicon nanosheets covered with org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
179
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 207 publications
(187 citation statements)
references
References 38 publications
(61 reference statements)
6
179
0
Order By: Relevance
“…We developed SiNSs modified with amino groups, and performed the amination reaction in an inert atmosphere, following a previously published method. 45) Internal structures were detected by XRD in the agglomerated n-decylamine (C10)SiNS state. A very strong narrow peak for C10SiNS was found at 2ª = 2.96°[ Fig.…”
Section: Regular Stacking Structure In Organic Modified Sinssmentioning
confidence: 99%
“…We developed SiNSs modified with amino groups, and performed the amination reaction in an inert atmosphere, following a previously published method. 45) Internal structures were detected by XRD in the agglomerated n-decylamine (C10)SiNS state. A very strong narrow peak for C10SiNS was found at 2ª = 2.96°[ Fig.…”
Section: Regular Stacking Structure In Organic Modified Sinssmentioning
confidence: 99%
“…[14][15][16][17] It has been previously shown that layered Zintl phases such as CaSi2 and CaGe2 can be topochemically deintercalated in aqueous HCl at low temperatures to produce layered silicon and germanium solids. [18][19][20] The resultant four-coordinate puckered lattice of Si and Ge atoms has an analogous geometry to sp 3 -hybridized graphane, or a Si/Ge(111) surface in which every Si/Ge atom is terminated with either -H or -OH above or below the layer. 18,21 There is a great propensity for the silicon lattice to oxidize, initially forming siloxene (SiH0.5(OH)0.5) sheets that are terminated with either Si-H or Si-OH bonds at the fourth coordination site, which eventually degrade to form SiO2 under ambient conditions.…”
mentioning
confidence: 99%
“…Researchers have recently developed layered van der Waals systems in which each surface atom requires a covalent ligand to become coordinatively saturated, such as the metal carbide/ nitride MXenes, the amine coordinated II-VI chalcogenides, and the group IV graphene analogues such as silicane or germanane 9,[16][17][18][19][20] . Because the valence/conduction bands of these materials are comprised of metal-metal or metal-anion bonding within the 2D plane 21 , rather than the p-bands such as that in graphene, these systems offer the possibility to tune the entire electronic properties on the basis of the identity and electron withdrawing capability of the substituent, without completely disrupting the relevant electronic states.…”
mentioning
confidence: 99%
“…The creation of many of these surface-terminated layered materials often relies on topotactic methods to interconvert a precursor layered crystal structure directly into the van der Waals material, frequently through deintercalation in acidic aqueous conditions that can result in partial surface termination with unwanted oxide or hydroxide states. For example, the deintercalation of layered Zintl phases, such as CaSi 2 in aqueous HCl produces the air and water reactive, partially hydroxide-terminated silicane SiH x (OH) 1 À x as evidenced by the existence of broad Si-O stretches that occur between 1,000-1,200 cm À 1 in the Fourier Transform Infrared (FTIR) spectrum 19,20 . This ambiguity in surface functionalization convolutes efforts to correlate the effects of surface functionalization on the optoelectronic properties of these single-atom thick semiconductors 9,20,[22][23][24] .…”
mentioning
confidence: 99%
See 1 more Smart Citation